Vertebrate tracks from the Paso Córdoba fossiliferous site (Anacleto and Allen formations, Upper Cretaceous), Northern Patagonia, Argentina: Preservational, environmental and palaeobiological implications - Díaz Martínez, Ignacio (2018)
Fil: Díaz Martínez, Ignacio. CONICET, Argentina.